Investigation of the antioxidant status and the number of double-stranded DNA breaks in models of brain tumor lesion by metastases of non-small cell lung cancer in vivo - E. V. Zaikina; I. A. Alliluev; Yu. N. Lazutin; Yu. V. Przhedetskiy; Yu. S. Shatova; M. A. Engibaryan; E. F. Komarova; D. A. Kharagezov; A. V. Galina; A. A. Kiblitskaya; M. V. Mindar; L. Z. Kurbanova (Исследования и практика в медицине, 2022)
Purpose of the study. Evaluation of the antioxidant status and DNA damage in tissues of subcutaneous xenografts of non-small cell lung cancer and in peritumoral tissues created using the A549 and H1299 cell cultures.Materials and methods. The study included 35 intact male Balb/c Nude immunodeficient mice. Cell lines A549 and H1299 were used as transplantable tumor biomaterial. A CDX model was created in accordance with the protocol for supratentorial injections (Ozawa T., James C. D., 2010) adapted for this experiment. Growth rates were controlled and intracranial xenografts were visualized using a high-resolution micro-CT system. The activity of catalase and superoxide dismutase was determined with non-denaturing electrophoresis in 8 % and 12 % polyacrylamide gel. The concentrations of sulfhydryl groups were determined according to Ellman. The DNA damage in lymphocytes was determined by the comet assay.Results. The experiment resulted in the creation of models of brain tumors characterized by intracranial growth pattern in 100 %. The activity of catalase in the studied lysates of intracranial xenografts, peritumoral tissue and healthy tissues of tumor-bearing animals in all experimental groups increased statistically significantly relative to the healthy tissue of intact animals, and the greatest differences from the control were recorded in the group of animals with implanted H1299 culture at a concentration of 1 × 106 . Superoxide dismutase activity in the studied lysates of intracranial xenografts and peritumoral tissues statistically significantly increased compared to the control sample in all experimental groups. The highest increase in the SOD activity was observed in the tissues of intracranial xenografts with the highest tumor load, which amounted to 28.8 % and 32.9 % of the changes relative to the control sample. A statistically significant increase in the concentration of SH-groups relative to the control sample in tumor tissue lysates was revealed in all experimental groups, and the highest concentration (36.2 ± 0.47) was observed in the group of experimental animals with the highest tumor load. Percentage change in tail moment (DNA damage indicator) in groups O1, O2, O3 and O4 increased statistically significantly compared to the control sample by 55.8 %, 111.8 %, 97.3 % and 170 %, respectively.Conclusions. The observed increase in the activity of the antioxidant defense system, accumulation of oxidative modifications of proteins, and an increase in DNA double-strand breaks in the tissues of intracranial xenografts of non-small cell lung cancer in vivo suggest that the created models reflect processes similar to those in tumors of human non-small cell lung cancer.